Experiences and Challenges of International Neurosurgical Residents in Germany - Omer, Mazin; Bissolo, Marco; El Rahal, Amir; Amirah, Ramy; Ahmed, Mamoun; Atallah, Oday; Machetanz, Kathrin; McLean, Anna C. Lawson; Nguyen, Thuy Linh; Alhamdan, Akram A.; Alnaggar, Ahmed; Beck, Jürgen; et al. (ELSEVIER SCIENCE INC, 2026)
OBJECTIVE: The number of international neurosurgical residents in Germany has significantly increased in recent years. This study investigates residents' satisfaction with the training program, factors contributing to dissatisfaction-including surgical exposure and psychological wellbeing-experiences of disparities, and future subspecialty preferences.
METHODS: A cross-sectional survey was conducted among neurosurgical residents in Germany. Data were collected from international residents and a control group of native German residents between 2023 and March 2024. An anonymous questionnaire was distributed via the German Society of Neurosurgery network and institutional email channels. Descriptive statistical analysis was performed.
RESULTS: A total of 85 international and 65 control group residents participated. International residents were predominantly male (79%), while the control group had a female majority (62%). More international residents worked in community hospitals (47%) versus university hospitals for controls (63%). Neuro-oncology was the most preferred subspecialty in both groups. About one-third of international residents reported moderate satisfaction with training, a level similar to that of the control group. However, limited surgical exposure (36%) and research opportunities (19%) were more frequently cited by international residents. Burnout was reported by 51% of international residents versus 89% of the control group (P < 0.0001). Race-based disparities were occasionally reported by 30% of international residents, yet 88% never filed a formal complaint, citing futility or fear of inaction. Despite high emotional strain in both groups, most residents did not consider psychological support necessary.
CONCLUSIONS: This study highlights training challenges in neurosurgery training. Key areas for improvement include increasing surgical exposure, expanding research opportunities, and improving reporting mechanisms for race-based disparities.